2013
DOI: 10.1017/s0033291713003000
|View full text |Cite
|
Sign up to set email alerts
|

Altered white-matter architecture in treatment-naive adolescents with clinical depression

Abstract: In line with neurocircuitry models of depression, our findings suggest that WM abnormalities within pathways facilitating cognitive and emotional functioning are involved in the pathophysiology of depression. Importantly, our findings show that these WM abnormalities are already present early in the course of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 72 publications
4
53
1
Order By: Relevance
“…The left UNC has been identified in several previous white matter microstructure analyses in pediatric depression (Aghajani et al, 2013;Bessette et al, 2014;Cullen et al, 2010;LeWinn et al, 2014) and symptom associations were found between FA in this tract and trait anxiety (Montag et al, 2012). Here, a negative relationship was found between children's self-reported depressive symptoms and FA.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The left UNC has been identified in several previous white matter microstructure analyses in pediatric depression (Aghajani et al, 2013;Bessette et al, 2014;Cullen et al, 2010;LeWinn et al, 2014) and symptom associations were found between FA in this tract and trait anxiety (Montag et al, 2012). Here, a negative relationship was found between children's self-reported depressive symptoms and FA.…”
Section: Discussionsupporting
confidence: 62%
“…Changes in the microstructure of the corpus callosum have also been reported by several studies but vary in the exact location with differences reported in the genu (Bessette et al, 2014;LeWinn et al, 2014) as well as the body (Aghajani et al, 2013;Bessette et al, 2014;LeWinn et al, 2014). Generally, lower FA is observed in these fibre bundles in the clinical group but increased FA has also been reported (Aghajani et al, 2013;Henderson et al, 2013). In addition to the above findings, a whole range of other fibre bundles have been reported by individual studies that have not yet been replicated (e.g., Bessette et al, 2014).…”
Section: Grey and White Matter Exhibit Differential Developmental Patmentioning
confidence: 75%
See 1 more Smart Citation
“…Damage to the white matter tracts of the temporal lobe have been correlated with many psychiatric and neurological conditions. For example, schizophrenia has been associated with abnormalities of the uncinate (UF), inferior fronto-occipital (IFOF) and inferior longitudinal (ILF) fasciculi (Catani et al, 2012;Fujino et al, 2014;Liu et al, 2013), while depression has also been found to correlate with abnormal fractional anisotropy in the UF (Aghajani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of white matter pathways connecting important brain regions of the limbic and the reward system may be associated with major depressive disorder (MDD) (Aghajani et al, 2013;Blood et al, 2010;Bracht et al, 2014c;de Diego-Adelino et al, 2014). Diffusion weighted magnetic resonance imaging (DW-MRI) enables white matter microstructure of the brain to be quantified non-invasively (Basser et al, 1994).…”
Section: Introductionmentioning
confidence: 99%